Detecting fraudulent financial reporting using financial ratio. Issue 2 (3rd October 2016) - Zainudin, Emie Famieza; Hashim, Hafiza Aishah
Abstract : Purpose: The main aim of this study is to analyse the financial ratio (i.e. financial leverage, profitability, asset composition, liquidity and capital turnover ratio) in detecting fraudulent financial reporting (FFR). Design/methodology/approach: The logit model was used to identify firms that are related to FFR. The sample firms that engage in fraudulent reporting were obtained from the media centre of Bursa Malaysia. The firms were selected based on their contravention of the Listing Requirements of Bursa Malaysia Securities Berhad. The data cover a period of seven years from 2007 to 2013. Findings: The results suggest that financial leverage, asset composition, profitability and capital turnover were significant predictors of FFR. Practical implications: The findings of this study may assist investors in making decision for their investments. Originality/value: This study describes firms that breach the Listing Requirements of Bursa Malaysia Securities Berhad using the financial ratio.